Effectiveness of Knowledge Management in Software Industries – An Empirical Study - Rekha, M; Rodrigues, Lewlyn L R (International Journal of Computer Sciences and Engineering, 2019)
The main aim of this study is to analyse the effectiveness of Knowledge Management in Software Industries. The Knowledge Management dimensions which could influence the organizational effectiveness have been identified. Metric to measure the relationship between these Knowledge Management dimensions has been developed. To test the hypotheses, a sample size of 254 software company employees has been collected and Partial Least Square technique of Structural Equation Modelling (SEM) has been used to investigate the empirical relationships between the different identified dimensions. Questionnaires were distributed to 300 employees of different software companies through Google Form. Response rate of 72% (254 employees responded) was achieved in the survey. The testing of hypotheses justified that in terms of organizational effectiveness, the identified dimensions of Knowledge Management are the critical success factors. Implications of the study would enable the Human Resource managers to make their Knowledge Management process more powerful for the enhancement of effectiveness of the organization. It may not be possible to generalize the results for the full extent, as the study limits itself to the number of software industries. All the limitations of statistical testing and modelling and simulation are applicable to this research.